Cluster of Infections Caused by Methicillin-Resistant Staphylococcus pseudintermedius in Humans in a Tertiary Hospital - Starlander, Gustaf (American Society for Microbiology, 2014)
The dog-associated Staphylococcus pseudintermedius is a rare pathogen in humans. Here we describe a cluster of infections caused by the methicillin-resistant S. pseudintermedius clone ST71-J-t02-II–III. It involved four elderly patients at a tertiary hospital. Three patients had wound infections, and the strain had a tendency to cause bullous skin lesions.